2022
DOI: 10.1007/s13571-022-00290-5
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Stock Portfolio Selection with a Multivariate Hidden Markov Model

Abstract: The underlying market trends that drive stock price fluctuations are often referred to in terms of bull and bear markets. Optimal stock portfolio selection methods need to take into account these market trends; however, the bull and bear market states tend to be unobserved and can only be assigned retrospectively. We fit a linked hidden Markov model (LHMM) to relative stock price changes for S&P 500 stocks from 2011-2016 based on weekly closing values. The LHMM consists of a multivariate state process whose in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
0
1
0
Order By: Relevance
“…It is especially crucial for precipitation modeling due to its less smooth spatial distribution compared to temperature. Majumder et al [31] used copula to estimate spatial correlations in HMMs, but this was conducted within the framework of maximum likelihood estimation using the Baum-Welch algorithm rather than in a Bayesian context. We would also like to use the reduced climate model output as a covariate of the model, as Robertson et al [6] did.…”
Section: Discussionmentioning
confidence: 99%
“…It is especially crucial for precipitation modeling due to its less smooth spatial distribution compared to temperature. Majumder et al [31] used copula to estimate spatial correlations in HMMs, but this was conducted within the framework of maximum likelihood estimation using the Baum-Welch algorithm rather than in a Bayesian context. We would also like to use the reduced climate model output as a covariate of the model, as Robertson et al [6] did.…”
Section: Discussionmentioning
confidence: 99%
“…They managed to highlight that a strategy calibrated based on HMM methodology works well even in periods of extreme volatility such as the one generated in 2020 by COVID-19 pandemic. Majumder & Neerchal (2022) has shown that the underlying market trends that drive stock price fluctuations are often referred to in terms of bull and bear markets. Optimal stock portfolio selection methods need to take into account these market trends; however, the bull and bear market states tend to be unobserved and can only be assigned retrospectively.…”
Section: 4mentioning
confidence: 99%